Determining the Effects of Pab1 Acetylation at K131 on Stress Granule Dynamics in Saccharomyces cerevisiae - Sivananthan, Sangavi (Université d'Ottawa / University of Ottawa, 2021)
Under environmental stress, such as glucose deprivation, cells form stress granules - the accumulation of cytoplasmic aggregates of repressed translational initiation complexes, proteins, and stalled mRNAs. Recent research implicates stress granules in various diseases, such as neurodegenerative disease, but the exact regulators responsible for the assembly and disassembly of stress granules are unknown. Studies detect post-translational modifications on core stress granule proteins. One modification is lysine acetylation, in which a substrate is regulated by a lysine acetyltransferase (KAT) and lysine deacetylase (KDAC). My project deciphers the impact of lysine acetylation on an essential protein found in stress granules, poly(A) binding protein (Pab1) in Saccharomyces cerevisiae. In this work, I demonstrated that acetylation mimic of Pab1-K131 reduces stress granule formation upon glucose deprivation, and other stressors such as ethanol, raffinose, and vanillin. A potential KDAC that might be facilitating this role is Rpd3. Further, electromobility shift assay studies suggest that acetylation mimic of Pab1-K131 negatively impacts poly(A) RNA binding. This work will be useful when exploring therapeutic options when combating diseases linked to stress granules.
Keywords: Pab1; Stress Granules; Glucose deprivation; Saccharomyces cerevisiae; Lysine acetylation; mRNA; KAT; KDAC; eIF4G1; Pab1-K131; Pab1-K131R; Pab1-K131Q